1990
DOI: 10.1288/00005537-199002000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The neurofasciocutaneous radial forearm flap in head and neck reconstruction: A preliminary report

Abstract: The radial forearm free flap has achieved considerable popularity as a reconstructive technique due to its thin, pliable tissue and long vascular pedicle. The successful use of this flap as a carrier of a vascularized nerve to bridge motor nerve gaps and as a sensate flap has not been previously reported in head and neck reconstruction. The superficial branch of the radial nerve was used as a vascularized nerve graft to bridge a facial nerve defect following radical parotidectomy. The medial and lateral antebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(56 citation statements)
references
References 34 publications
0
51
0
5
Order By: Relevance
“…Ten years later, Matloub et al, 16 with the use of reinnervated lateral arm flaps, reported the restoration of sensation in 2 of the 4 flaps used for intraoral reconstruction. Urken et al 17 reported the successful transfer of a sensate radial forearm free flap for pharyngeal reconstruction through the anastomosis of the antebrachial cutaneous nerves to the great auricular nerve. With the use of the same flap, Dubner and Heller 18 reported high-fidelity restoration of intraoral sensation.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Ten years later, Matloub et al, 16 with the use of reinnervated lateral arm flaps, reported the restoration of sensation in 2 of the 4 flaps used for intraoral reconstruction. Urken et al 17 reported the successful transfer of a sensate radial forearm free flap for pharyngeal reconstruction through the anastomosis of the antebrachial cutaneous nerves to the great auricular nerve. With the use of the same flap, Dubner and Heller 18 reported high-fidelity restoration of intraoral sensation.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…En cuanto a la inclusión de ramas nerviosas en el colgajo, la incorporación de los ramos cutáneos medial ó lateral antebraquiales, permiten restablecer la sensación al anastomosarlo a ramos sensitivos cervicofaciales, 16 . Por otro lado se ha descrito el uso de un segmento y las ramas terminales del nervio cutáneo radial como injerto nervioso vascularizado para la reconstrucción de la continuidad del tronco del nervio facial junto al defecto cutáneo.…”
Section: Discussionunclassified
“…16 Moreover, the use of a segment and the terminal branches of the radial cutaneous nerve has been described as a vascularized nerve graft for reconstructing the continuity of the facial nerve trunk together with the cutaneous defect. 17 The main inconvenience of the radial forearm free flap lies in the need for a partial skin graft for closing the donor area, which results in aesthetic deformity and a delay in healing, although muscle flaps and tissue expanders can be used in order to avoid this.…”
Section: Discussionmentioning
confidence: 99%
“…It is versatile in that it also may be transferred as a sensory flap incorporating the medial or lateral antebrachial cutaneous nerve, 8,9 or a composite bone flap using vascularized radius. [10][11][12] It also may include vascularized tendon 13 and brachioradialis muscle.…”
Section: Commonly Used Microvascular Free Flaps Radial Forearm Flapmentioning
confidence: 99%